Liberation Theology as a Revolutionary Ideology in Latin America - Jacobson, Roberta Steinfeld (Tufts Archival Research Center, 2005)
Volume 10, Issue 2. Summer The doctrine of liberation theology in Latin American revolutionary movements has sought to bridge the gap between Marxism and Catholicism, by blending religious dogma and Marxist theory into a plan of action for improving social conditions. Roberta Steinfeld Jacobson outlines the attitudes both of the Catholic Church and the Soviet Union toward this hybrid doctrine. She then shows that liberation theology effectively promotes revolution but so far has been unable to survive as an alternative to traditional Catholic doctrine after the first phase of a revolutionary struggle is over. She concludes with a discussion of policy recommendations for the American government in coping with the influence of liberation theology on revolutionary movements.